New challenges for Europe: migration, security and citizenship rights - Anna Triandafyllidou (Revista CIDOB d'Afers Internacionals, 2005)
After the relative prominence of multicultural citizenship theoretical debates and multicultural policy developments in the 1990s, we witness today a change of direction. This crisis of multiculturalism comes at a time of heightened security awareness as a result of the 9/11 events and their aftermath. The upsurge of international terrorism has led to the increasing securitisation of migration agendas. This paper discusses critically the emergence of a climate of high security awareness in Europe through the analysis of three, in my view, inter-related issues: the overall securitisation of migration; the securitisation of Europe; and the reluctance of EU countries to concede to third country nationals who are long-term residents in their territories, a common status of ‘civic citizenship’ – what has been called in the related directive the ‘long-term resident status’ – that would include a substantial set of rights, comparable to those of EU citizens. The paper highlights howthe link between terrorism, migration and security is discursively constructed and argues that too much attention to security and too little attention to rights is detrimental to the state of European democracies.